PENINGKATAN PEMAHAMAN KONSEP MATEMATIKA PESERTA DIDIK DENGAN MENGGUNAKAN BLOK ALJABAR - Resti Novita Sari (Jurnal Edukasi dan Penelitian Matematika, 2018)
Understanding of mathematical concepts of students in seventh grade of SMPN 17 Padang is still low, so it needs to be improved. Algebra Blocks is manipulatives that can improve students' understanding of mathematical concepts in abstract topics. The aims of this research describes whether the understanding of mathematical concepts of students that study by Algebra Blocks is better than conventional learning in grade VII SMPN 17 Padang. The kind of this research is quasi eksperiment with static grup design. The samples are the students at class VII.4 and VII.3. The result of the research show that understanding of mathematical concepts of students that study by Algebra Blocks is better than conventional learning. Keywords – algebra blocks, conventional learning, understanding of mathematical concept.